Primary cemented bipolar hemiarthroplasty by transtrochanteric approach in unstable intertrochanteric fractures - Skariah, Thomas Angelo; George, Koshy; Mathew, Deny; George, James C.; Chittaranjan, Samuel (International Journal of Research in Orthopaedics, 2021)
Background: The successful treatment of unstable intertrochanteric fractures of the femur in elderly patients is a challenge. Due to complications associated with internal fixation, primary hemiarthroplasty is increasingly becoming an alternative treatment to achieve early mobilisation. A transtrochanteric approach could potentially decrease the complications associated with primary hemiarthroplasty. Aim of the study is to document the postoperative outcome and complications associated with this treatment. Methods: In this retrospective study, all elderly patients with unstable trochanteric fractures, treated by primary hemiarthroplasty through a transtrochanteric approach, in a tertiary care centre, from September 2017 to December 2019, were enrolled. Their data from hospital records were analysed and results compared to literature. Results: 48 patients underwent the procedure. Average age was 85 years. One year mortality was 31.25%. Average duration of surgery is 85 min. 58.3% were ambulant at one year. One case of dislocation secondary to surgical site infection was present. Conclusions: Primary hemiarthroplasty as a primary treatment in this group of patients enables early mobilization and prevents complications associated with prolonged immobilization. Transtrochanteric approach reduces the duration of surgery. Achieving early ambulation is the key to successful treatment.